Long-term economic evaluation of the recombinant Mycobacterium tuberculosis fusion protein (EC) test for the diagnosis of Mycobacterium tuberculosis infection - Diao, Sha; Liu, Zheng; Liu, Dan; Cheng, Xiao; Zeng, Linan; Jiao, Xue-Feng; Chen, Zhe; Ni, Xiaofeng; He, Siyi; Wu, Bin; Kang, Deying; Wan, Chaomin; et al. (Frontiers in Pharmacology, 2023)
Background: Tuberculosis continues to be a significant global burden. Purified Protein Derivative of Tuberculin (TB-PPD) is one type of tuberculin skin test (TST) and is used commonly for the auxiliary diagnosis of tuberculosis. The Recombinant Mycobacterium Tuberculosis Fusion Protein (EC) test is a new test developed in China. Objective Evaluate the long-term economic implications of using the EC test compared with the TB-PPD test to provide a reference for clinical decision-making. Methods: The target population was people at a high risk persons of being infected with M. tuberculosis. The outcome indicator was quality-adjusted life years (QALY). A cost–utility analysis was used to evaluate the long-term economic implications of using the EC test compared with the TB-PPD test. We employed a decision tree–Markov model from the perspective of the whole society within 77 years. Results: Compared with the TB-PPD test, the EC test had a lower cost but higher QALY. The incremental cost–utility ratio was −119,800.7381 CNY/QALY. That is, for each additional QALY, the EC test could save 119,800.7381 CNY: the EC test was more economical than the TB-PPD test. Conclusion: Compared with the TB-PPD test, the EC test would be more economical in the long term for the diagnosis of M. tuberculosis infection according our study.